2020
DOI: 10.1007/978-3-030-52237-7_29
|View full text |Cite
|
Sign up to set email alerts
|

Moodoo: Indoor Positioning Analytics for Characterising Classroom Teaching

Abstract: This paper presents Moodoo, a system that models how teachers make use of classroom spaces by automatically analysing indoor positioning traces. We illustrate the potential of the system through an authentic study aimed at enabling the characterisation of teachers' instructional behaviours in the classroom. Data were analysed from seven teachers delivering three distinct types of classes to + 190 students in the context of physics education. Results show exemplars of how teaching positioning traces reflect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…For example, ClassBeacons [3] deployed tracking devices to teachers and tables around a classroom to model the time teachers spent with each group of students. Similar work is shown in Moodoo [29], an automatic system that models teachers' positioning strategies in a classroom. The authors demonstrated that these tracking devices can be used to generate physical positioning analytics in various learning settings, including collaboration, simulation, and laboratory learning spaces [30].…”
Section: Indoor-sensing Technologies and Learning Analyticsmentioning
confidence: 79%
See 2 more Smart Citations
“…For example, ClassBeacons [3] deployed tracking devices to teachers and tables around a classroom to model the time teachers spent with each group of students. Similar work is shown in Moodoo [29], an automatic system that models teachers' positioning strategies in a classroom. The authors demonstrated that these tracking devices can be used to generate physical positioning analytics in various learning settings, including collaboration, simulation, and laboratory learning spaces [30].…”
Section: Indoor-sensing Technologies and Learning Analyticsmentioning
confidence: 79%
“…Positioning tracking often suffers from missing values due to occlusion or detachment of trackers [15]. Therefore, linear interpolation was used to fill in any missing values between two valid data points, and with a limit of 60 consecutive missing values [29]. For a meaningful attendance, students' positioning must not be missing for more than ten minutes; otherwise, they are excluded from the analysis for that session since it most likely meant that the student did not come to session and their tracker was put away or they were outside of the tracking area during the period, and therefore not attending the session.…”
Section: Modelling From Positioning Data To Interactions and Social Tiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Current learning analytics (LA) research has identified that classroom analytics can support learning outcomes and teacher awareness [1,4,14,17,19]. These studies have investigated the importance of analyzing the interactions between the teacher, students, and the space during classroom instruction.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have investigated the importance of analyzing the interactions between the teacher, students, and the space during classroom instruction. The resulting analyses can provide meaningful feedback to teachers by making teacherstudents' interactions visible [1,5,17], improving teachers' awareness and directing attention to struggling students [4,12,13], or giving early alerts about students' progress and engagement [5,9,13].…”
Section: Introductionmentioning
confidence: 99%